Edge plasma responses to energetic-particle-driven MHD instability in Heliotron J. (2nd December 2015) - Ohshima, S.; Kobayashi, S.; Yamamoto, S.; Nagasaki, K.; Mizuuchi, T.; Okada, H.; Minami, T.; Hashimoto, K.; Shi, N.; Zang, L.; Kasajima, K.; Kenmochi, N.; et al.
Abstract: Two different responses to an energetic-particle-driven magnetohydrodynamic (MHD) instability, modulation of the turbulence amplitude associated with the MHD instability and dynamical changes in the radial electric field ( E r ) synchronized with bursting MHD activities, are found around the edge plasma in neutral beam injection (NBI) heated plasmas of the Heliotron J device using multiple Langmuir probes. The nonlinear phase relationship between the MHD activity and broadband fluctuation is found from bicoherence and envelope analysis applied to the probe signals. The structural changes of the E r profile appear in perfect synchronization with the periodic MHD activities, and radial transport of fast ions are observed around the last closed flux surface as a radial delay of the ion saturation current signals. Moreover, distortion of the MHD mode structure is clarified in each cycle of the MHD activities using beam emission spectroscopy diagnostics, suggesting that the fast ion distribution in real and/or velocity spaces is distorted in the core plasma, which can modify the radial electric field structure through a redistribution process of the fast ions. These observations suggest that such effects as a nonlinear coupling with turbulence and/or the modification of radial electric field profiles are important and should be incorporated into the study of energetic particle driven instabilities in burning plasma physics.